Organic Carbon Mineralization and Bacterial Community of Active Layer Soils Response to Short-Term Warming in the Great Hing’an Mountains of Northeast China - Dong, Xingfeng; Liu, Chao; Ma, Dalong; Wu, Yufei; Man, Haoran; Wu, Xiangwen; Li, Miao; Zang, Shuying (Frontiers in Microbiology, 2021)
As a buffer layer for the energy and water exchange between atmosphere and permafrost, the active layer is sensitive to climate warming. Changes in the thermal state in active layer can alter soil organic carbon (SOC) dynamics. It is critical to identify the response of soil microbial communities to warming to better predict the regional carbon cycle under the background of global warming. Here, the active layer soils collected from a wetland-forest ecotone in the continuous permafrost region of Northeastern China were incubated at 5 and 15 °C for 45 days. High-throughput sequencing of the 16S rRNA gene was used to examine the response of bacterial community structure to experimental warming. A total of 4148 OTUs were identified, which followed the order 15°C > 5°C > pre-incubated. Incubation temperature, soil layer and their interaction have significant effects on bacterial alpha diversity (Chao index). Bacterial communities under different temperature were clearly distinguished. Chloroflexi, Actinobacteria, Proteobacteria, and Acidobacteria accounted for more than 80% of the community abundance at the phylum level. Warming decreased the relative abundance of Chloroflexi and Acidobacteria, while Actinobacteria and Proteobacteria exhibited increasing trend. At family level, the abundance of norank_o__norank_c__AD3 and Ktedonobacteraceae decreased significantly with the increase of temperature, while Micrococcaccac increased. In addition, the amount of SOC mineralization were positively correlated with the relative abundances of most bacterial phyla and SOC content. SOC content was positively correlated with the relative abundance of most bacterial phyla. Results indicate that the SOC content was the primary explanatory variable and driver of microbial regulation for SOC mineralization. Our results provide a new perspective for understanding the microbial mechanisms that accelerates SOC decomposition under warming conditions in the forest-wetland ecotone of permafrost region.